The unreliable father effect: intrapersonal communication as identity pillar for fatherless daughters - Grisel Aranis; Ayunintyas, Fitria; Istiyanto, S. Bekti (Faculty of Communications Science, Dr. Soetomo University, 2026)
This study explored the intrapersonal communication dynamics of fatherless girls in facing life struggles using intrapersonal communication theory. A descriptive qualitative method was used with purposive sampling to select informants. Data analysis followed the five stages by Colaizzi and Moustakas: initial stage, horizontalisation, clustering meanings, essence description, and reporting. Data was collected by conducting observation and in-depth interviews with five informants residing near Jakarta, then transcribed and analysed using NVIVO 14. The research results indicate that fatherlessness, particularly within the unreliable father category, affects self-perception—causing insecurity, low self-esteem, and indecisiveness. Despite similar backgrounds, each informant experienced unique impacts. With sufficient understanding of intrapersonal communication, the informants developed self-defence mechanisms to face pressures and challenges. This study highlights the role of intrapersonal communication as a psychological coping tool that helps fatherless girls adapt and build resilience in their lives.